2021
DOI: 10.1111/add.15712
|View full text |Cite
|
Sign up to set email alerts
|

Support for Aboriginal health services in reducing harms from alcohol: 2‐year service provision outcomes in a cluster randomized trial

Abstract: Background and aims: There is a higher prevalence of unhealthy alcohol use among Indigenous populations, but there have been few studies of the effectiveness of screening and treatment in primary health care. Over 24 months, we tested whether a model of service-wide support could increase screening and any alcohol treatment.Design: Cluster-randomized trial with 24-month implementation (12 months active, 12 months maintenance).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…However, to our knowledge this is the first controlled trial to report on the effect of a service-level alcohol screening implementation program on screening regularity, in addition to screening rate. We previously showed that the odds of a patient being screened in any 2-month period significantly increased during the 24 months of implementation of support in this cluster randomised trial [ 12 ]. However, in this report we show that this increase in screening rate was not reflected in an increase in odds of previously unscreened clients in the early-support arm being screened for the first time or of clients receiving regular annual screening when compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, to our knowledge this is the first controlled trial to report on the effect of a service-level alcohol screening implementation program on screening regularity, in addition to screening rate. We previously showed that the odds of a patient being screened in any 2-month period significantly increased during the 24 months of implementation of support in this cluster randomised trial [ 12 ]. However, in this report we show that this increase in screening rate was not reflected in an increase in odds of previously unscreened clients in the early-support arm being screened for the first time or of clients receiving regular annual screening when compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Training included: harms related to alcohol; current evidence for screening; culturally secure and accurate administration and interpretation of AUDIT-C; use of annual AUDIT-C screening; responding to a positive AUDIT-C screen; and using service-wide screening data to monitor improvements in screening Implementation approaches incorporated cultural protocols of Aboriginal and Torres Strait peoples such as gender appropriateness, kinship systems and cultural obligations Face-to-face workshops were delivered by an addiction medicine specialist and an Aboriginal health professional (e.g., drug and alcohol worker or other) 4 Data feedback report, based on the bi-monthly data provided by services Graphic representation of proportion of clients screened; proportion drinking at risky levels as measured by AUDIT-C; as well as overall rate of screening over 2-month periods and the last 12-months; and recorded treatment provided Presented as a pdf file with graphics and emailed to service champions and key contacts 5 Bi-monthly teleconference for service champions to exchange improvement ideas and experiences 6 Support to modify practice software to facilitate screening such as inclusion of AUDIT-C in the Adult Health Check, and other electronic forms used for periodic and opportunistic health checks, e.g., over 50 s, pregnancy, pre-consult examination 7 A website with a repository of electronic tools and resources, including screening resources and standard drinks charts, and a private chat platform for champions 8 Financial support for purchase of agreed resources e.g., standard drink cups, clinical handbooks, prevention materials a This table emphasises the screening-specific content of the support model. Fuller description, including elements supporting alcohol treatment, has been published elsewhere [ 12 , 15 ] …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations